Legal Aspects of Military and Defence Applications of Artificial Intelligence Within the European Union - Jurić, Marko (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
This chapter aims to map the primary legal instruments relevant to governing the use of artificial intelligence (AI) for military and defence purposes in Europe. The analysis indicates that, while there is no lack of regulation, the legal framework itself should not pose insurmountable obstacles for the industry and entities operating within the military and defence sectors. This issue is particularly evident in the regulation of lethal autonomous weapons systems (LAWS). There are no binding EU rules on this matter in the European Union (EU); however, some European institutions are advocating for reasonable safeguards to enhance human control and accountability.The drafters of the EU AI Act have made concerted efforts to exempt the military, defence, and national security sectors from its scope. However, this does not mean that all AI-related activities in these domains will escape scrutiny by the Court of Justice of the European Union (CJEU). As existing case law demonstrates, the Court has in various areas under the primary competence of Member States, including matters of national defence. Therefore, it is possible that a similar approach may be applied in AI-related cases.Finally, the most significant challenges in developing and using AI in the military and defence domains may arise from rules governing data usage. This chapter demonstrates that the current EU laws apply within the military and defence sectors. The possibilities for excluding their application appear narrower than in AI Act, particularly given the CJEU’s established case law. Combined with the broad concept of personal data, it is easy conceivable that personal data protection rules could substantially impact the capacity of national defence and military entities to process certain data.Keywords: Artificial intelligence, AI, military AI, defence AI, personal data, AI Act